Corrosion detection using piezoelectric wafer active sensors - Morsin, Mohamad Naquib; Nor Ayob, Nor Muzakkir; Abdul Rahim, Ruzairi; Ahmad, Nasarudin; Sahlan, Shafishuaza; Leow, Pei Ling; Md. Yunus, Yusri (Penerbit UTHM, 2016)
In everyday life, the various sectors and activities are vulnerable to the effects of corrosion such as water supply sector, the industrial sector involving pipelines and oil and gas sectors. Reaction of electrochemical oxidation of the metal in reaction with an oxidant such as oxygen or sulfur is the main cause of corrosion. The various studies carried out to determine whether the condition of a material can be used or dangerous to use. Currently, there are two categories that are appropriate to solve this problem that is internal or external inspection. The first category of internal inspection, scanning is focused on one point, which is a method common to use the pipeline; it's mounted on a rotating transducer. The second category is the external inspection, this method is able to scan the parallel point, but when pipes are in use have the insulator, the insulator must be removable for the purpose of scanning and reinstall when finished scanning [1]. There are various methods that have been used in improving the reading count this corrosion. Among these are pitch-catch method that is used to detect corrosion on aluminum structures, pulse-echo method to detect corrosion in pipes and guided ultrasonic waves combined with BEM numerical simulation is used to detect hidden corrosion [2]. This paper will present multiple modes in-situ method using Piezoelectric Wafer Active Sensors transducers with impedance, pitch-catch and pulse-echo damage detection method for either corrosion or cracks in metallic plate structures [3] [4].